EXAMINING THE RELATIONSHIP BETWEEN COMMERCIAL BANKING PRACTICES AND FINANCIAL STABILITY - Murad Ahmed; Muhammad Farhan Aslam; Maira Khalid; Dr Hamid Khan; Taimur Ashiq (International Journal of Contemporary Issues in Social Sciences, 2024)
Background: Examining the relationship between commercial banking practices and financial stability involves analyzing how various banking activities, risk management strategies, and regulatory compliance measures impact the overall health and resilience of the financial system. Objective: This study aims to identify key practices that contribute to or undermine financial stability, providing insights for policymakers and industry stakeholders to enhance economic robustness. Methods: The study's respondents were chosen at random from among commercial bank senior management. Two senior managers from each bank received questionnaires, for a total sample size of 82 responses. The questionnaires were distributed using a drop-and-pick technique by the researcher. The features of the variables under research were captured and quantitative data was analyzed using descriptive statistics, such as means and frequencies. In addition, the link between the independent and dependent variables was ascertained by the application of inferential statistics like regression and correlation. Results: Financial stability was shown to be impacted by the operational costs of commercial banks, bank size, board size, capital size, prudent interest rate policy, and productive staff. According to the model summary, internal variables together were responsible for 26.3% of the variation in financial stability. Furthermore, external determinants influencing financial stability were found to include interest rates, inflation rates, interest rate spreads, currency rates, and GDP growth, which accounted for 29.1% of the variation. The findings also demonstrated how commercial banks improved their financial stability through the application of financial innovations, bank policy, income diversification, financial reconciliation, and supervision. Conclusion: In conclusion, both internal and external factors significantly influence commercial bank financial stability, with banks enhancing stability through financial innovations, policy measures, income diversification, financial reconciliation, and supervision.